Congenital cystic adenomatoid malformation (CCAM): antenatal and postnatal management - Kanavi, Jayashree V.; Thangaraj, Jasmine; Thomas, Annamma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Congenital cystic adenomatoid malformation (CCAM) is a rare abnormality of lung development. The estimated incidence ranges from 1: 10,000 to 1.35,000 live births. It is diagnosed by prenatal screening at 18-20 weeks of gestation. Surgical excision of symptomatic lesions is relatively straight forward, but management of asymptomatic lesions is controversial. Methods: Among women who delivered at St. Johns medical college and hospital, Bangalore between Jan 2011 to Dec 2016, those with the diagnosis of CCAM during anomaly scan were included in the study. Antenatal and Post-natal period and their outcomes were evaluated. Follow up was extend up to the childhood in the affected foetus. Results: There were 5 cases of CCAM in 13057 deliveries during 5-year study. Incidence was 1:2611. Mean gestational age at diagnosis was 21.6±2.5weeks. All foetus had CVR (CCAM volume) ratio more than 1.6 and there was no compromise on lung volume. Mean lung volume was 62.8±8.6 cc. and mean Apgar score at 1minute was 6.8±2.7 and at 5 minutes was 8.0±2.2. Among 5 foetuses, 2 foetuses had regression of cyst by birth and 3 underwent surgery for resection after birth. Conclusions: CCAM remains a challenge for obstetricians, neonatologists and paediatric surgeons. The combination of prenatal MRI and serial ultrasound studies optimize foetal surveillance and postnatal care. In asymptomatic CCAM, babies should be followed up to adolescence and adulthood, as they can manifest with malignant changes.